Low Molecular Weight Heparin Modulates Maternal Immune Response in Pregnant Women and Mice with Thrombophilia. (11th December 2014) - Luley, Lydia; Schumacher, Anne; Mulla, Melissa J.; Franke, Dirk; Löttge, Michael; Fill Malfertheiner, Sara; Tchaikovski, Svetlana N.; Costa, Serban‐Dan; Hoppe, Berthold; Abrahams, Vikki M.; Zenclussen, Ana C.
<x xml:space="preserve">Abstract</x> Problem Thrombophilia is associated with pregnancy complications. Treatment with low molecular weight heparin (LMWH) improves pregnancy outcome, but the underlying mechanisms are not clear. Methods of study We analyzed Treg frequency in blood from thrombophilic pregnancies treated with LMWH (n = 32) or untreated (n = 33) and from healthy pregnancies (n = 39) at all trimesters. Additionally, we treated pregnant wild‐type, heterozygous and homozygous factor‐V‐Leiden (FVL) mice with LMWH or PBS and determined Treg frequency, pro‐/anti‐inflammatory cytokine levels and Caspase‐3‐activity in placenta and decidua. Results Treg frequencies were increased in second and third trimester in LMWH‐treated thrombophilic pregnancies compared to controls. Treg levels were comparable to those of normal pregnancies. Homozygous FVL mice had decreased decidual Tregs compared to wild‐type mice. LMWH treatment normalized Tregs and was associated with increased decidual IL‐10 mRNA. LMWH diminished Caspase‐3‐activity in mice of all genotypes. Conclusion We demonstrated anti‐apoptotic and anti‐inflammatory effects of LMWH in pregnant FVL mice. LMWH increased Treg levels in mice and humans, which suggests benefits of LMWH treatment for thrombophilic women during pregnancy.